A PLATONIC METHOD FOR MAKING IDEAS ENGAGING AND ACCESSIBLE. Issue 40 (9th April 2015) - More, Charles
Abstract : In this essay, I introduce an imaginative method for transforming reasoned arguments of specialists into a form that is engaging and accessible to nonspecialists. I begin by reviewing a passage in Plato in which the method is used. I then develop an example of the method for a modern context. I conclude with reasons that philosophy ought to concern itself to engage the general public using imaginative methods of this kind.